DISSECTION OF YIELD AND FIBER QUALITY TRAITS UNDER DROUGHT CONDITION IN GOSSYPIUM HIRSUTUM L. - IQBAL, J; KHALID, MN; RIAZ, S; RAZAQ, A; SHAKOOR, A; KARIM, A; RAZZAQ, B; GOHAR, MB; AQEEL, M; MAJEED, T (Biological and Clinical Sciences Research Journal, 2023)
Moisture is a significant component in cotton growth and yield, but stress is the main factor limiting crop productivity since it has a negative impact on cotton’s ability to produce high-quality fiber as well as square/boll and lint output. Reduced water availability during the development of the bolls could lead to drastically decreased yield. Four cotton genotypes (MNH-1020, FH-114, BH-178 and CIM-602) were grown under regular irrigation and water-deficit circumstances to examine the tolerance to water scarcity. To further understand the impacts of water shortage, four watering treatments were used in this study: control 100% field capacity, 70% field capacity, 60% field capacity, and 40% field capacity at the squaring stage till boll formation. As the amount of soil moisture declines, we have observed fall in fiber length, fiber fineness, and fiber strength. Yield/plant reduced under water stress due to less no of flowers and bolls, but also because of reduced boll weight. When the stress was extreme during the reproductive growth stage. MNH-1020 showed drought tolerance as by exhibiting maximum yield, boll weight and fiber characters when compared to other three varieties, while FH-114 being second. CIM-602 showed drought susceptibility as it exhibited least no of bolls/plant, yield/plant and boll weight.